MEASUREMENT IN LATVIAN SCHOOL MATHEMATICS EDUCATION - Karklina, Vaira (Acta Paedagogica Vilnensia, 2015)
This article covers some aspects related to teaching measurement in school mathematics, the reflection of the issues of mathematical measurements in regulatory documents and national curricula, peculiarities of teaching the topic and opportunities for improving the teaching methods, as well as the experience gained during the development of the study project on teaching measures to future teachers of mathematics.
Keywords: measures; measuring; standards; programmes; projects